Tracing site-specific isotopic signatures along a Blue Tit Cyanistes caeruleus food chain - Charmantier, Anne; Blondel, Jacques; Perret, Philippe; Harmelin-Vivien, Mireille (IBIS, 2014)
Food chains culminating with temperate insectivorous passerines are well described, yet whether trophic webs can be site-specific remains a largely unexplored question. In the case of site- or habitat-specificity of food webs, stable isotope signatures of bird feathers may enable assignment of unmarked individuals to a site or a habitat of origin. We address this question in landscapes that include contrasting forest habitat patches with either deciduous Downy Oak Quercus humilis or evergreen Holm Oak Quercus ilex as dominant tree species. First, we examine the spatial variation across habitats and sites in the stable isotope ratios of carbon (C-13) and nitrogen (N-15) along the oak leaf-Tortrix moth Tortrix viridana caterpillar-Blue Tit Cyanistes caeruleus food chain. Secondly, we assess whether the isotopic signatures allow for correct assignment of individual birds to their site or habitat of origin. At the scale of the landscape, stable isotope values enabled identification of the different components of the Blue Tit food chain: from oak leaves to Blue Tit nestlings and yearling birds. However, isotopic signatures were site-specific (i.e. geographical) more than habitat-specific (i.e. deciduous vs. evergreen oaks). Discriminant analyses correctly assigned 85% of nestlings and 83% of resident yearling birds, indicating a pronounced effect of site on Blue Tit feather isotopic signatures. We thereby demonstrate that isotopes reflect a stronger association of locally born birds to the local features of their habitat than that of un-ringed yearling birds, whose plumage may have grown while in a wider geographical area. This study provides evidence of site-specific isotopic signatures from oak leaves to Blue Tit feathers at a fine spatial scale.
The following values have no corresponding Zotero field: pub-location: 111 RIVER ST, HOBOKEN 07030-5774, NJ USA publisher: WILEY-BLACKWELL
Keywords: environment heterogeneity; habitat-specific isotopic signature; natal dispersal; trophic ecology

Food supplementation in distinct Corsican oak habitats and the timing of egg laying by Blue Tits - Bourgault, Patrice; Perret, Philippe; Lambrechts, Marcel M (JOURNAL OF FIELD ORNITHOLOGY, 2009)
Resource constraints may impose physiological limitations on egg production and influence the timing of breeding in seasonally breeding birds. Food-supplementation experiments have demonstrated that food availability may influence the timing of egg laying, but the moderate response of birds in most studies suggests that the effect of food availability may be apparent only under certain ecological conditions. Experiments conducted in habitats that differ in ecological characteristics and natural availability of food sources are, therefore, needed to effectively examine the possible role of habitat-specific physiological constraints on the timing of breeding. We compared the response of Blue Tits (Cyanistes caeruleus) to supplemental feeding in four oak woodlands that differed in elevation, forest type, and food availability on the island of Corsica. We found that supplemental feeding advanced the date of egg laying (by about 1 week) at only one of four sites; a site dominated by evergreen holm oak where the availability of natural food was likely lower than at the other sites. Our results suggest that the response of Blue Tits to supplemental food depends on the natural level of resource abundance, but, in addition, that the effect of supplemental feeding on the timing of breeding appears to be small compared to the typical and, for our study sites, great (> 1.5 mo) between-population variation in clutch initiation dates. Physiological limitations related to the acquisition of nutrients and energy may exert only a limited effect on the onset of breeding, and behavioral flexibility in the integration of fine-scale environmental signals (e.g., temperature and phenology) that predict future breeding conditions may be more important in explaining variation among populations in the timing of breeding.
Keywords: Blue tit; food constraints; food supplementation; proximate factors; timing of breeding

Food supplementation in distinct Corsican oak habitats and the timing of egg laying by Blue Tits - Bourgault, Patrice; Perret, Philippe; Lambrechts, Marcel M. (JOURNAL OF FIELD ORNITHOLOGY, 2009)
Resource constraints may impose physiological limitations on egg production and influence the timing of breeding in seasonally breeding birds. Food-supplementation experiments have demonstrated that food availability may influence the timing of egg laying, but the moderate response of birds in most studies suggests that the effect of food availability may be apparent only under certain ecological conditions. Experiments conducted in habitats that differ in ecological characteristics and natural availability of food sources are, therefore, needed to effectively examine the possible role of habitat-specific physiological constraints on the timing of breeding. We compared the response of Blue Tits (Cyanistes caeruleus) to supplemental feeding in four oak woodlands that differed in elevation, forest type, and food availability on the island of Corsica. We found that supplemental feeding advanced the date of egg laying (by about 1 week) at only one of four sites; a site dominated by evergreen holm oak where the availability of natural food was likely lower than at the other sites. Our results suggest that the response of Blue Tits to supplemental food depends on the natural level of resource abundance, but, in addition, that the effect of supplemental feeding on the timing of breeding appears to be small compared to the typical and, for our study sites, great (> 1.5 mo) between-population variation in clutch initiation dates. Physiological limitations related to the acquisition of nutrients and energy may exert only a limited effect on the onset of breeding, and behavioral flexibility in the integration of fine-scale environmental signals (e.g., temperature and phenology) that predict future breeding conditions may be more important in explaining variation among populations in the timing of breeding.
The following values have no corresponding Zotero field: pub-location: COMMERCE PLACE, 350 MAIN ST, MALDEN 02148, MA USA publisher: WILEY-BLACKWELL PUBLISHING, INC
Keywords: Blue tit; food constraints; food supplementation; proximate factors; timing of breeding

Why do Corsican Blue Tits Cyanistes caeruleus ogliastrae not use nest boxes for roosting? - Dhondt, André a.; Blondel, Jacques; Perret, Philippe (Journal of Ornithology, 2009)
We compared winter roosting behaviour of Blue Tits Cyanistes caeruleus in the mainland of southern France and on the island of Corsica in small-holed nest boxes. While in southern France Blue Tits use nest boxes for roosting, Corsican Blue Tits do not. We suggest that this behaviour is innate because Corsican wild-caught as well as F1 and F2 birds born in captivity do not use nest boxes in aviaries even when kept adjacent to mainland tits that sleep in boxes. We suggest that the cost/beneﬁt balance differs between mainland France and Corsica: in Corsica, the costs of roosting in the canopy are less than in mainland France because (1) predators, e.g. owls, are rare in Corsica while abundant on the mainland, (2) the permanent evergreen foliage of the dominant tree in Corsica, the holm oak, could be preferred to nest boxes which are not risk-free, and (3) the costs of using cavities for roosting could be higher in Corsica because of increased mammal predator pressure and higher ectoparasite load than on the mainland.
Keywords: á parasitism á; Cyanistes caeruleus ogliastrae; cyanistes caeruleus ogliastrae á; Life-history trait; life-history trait á predation; Parasitism; Predation; Small-holed nest box

Habitat quality as a predictor of spatial variation in blue tit reproductive performance: a multi-plot analysis in a heterogeneous landscape - Lambrechts, MarcelM; Caro, Samuel; Charmantier, Anne; Gross, Nicolas; Galan, Marie-Jo; Perret, Philippe; Cartan-Son, Mireille; Dias, PaulaC; Blondel, Jacques; Thomas, DonaldW (Oecologia, 2004)
Vertebrate studies have rarely investigated the influence of spatial variation in habitat richness on both short-term (breeding) and long-term (offspring recruitment) reproductive performance using simultaneously multi-patch, multi-habitat type and multi-year approaches at landscape level. Here we present results of such an approach using the influence of two oak tree (Quercus ilex, Q. humilis) species on reproductive performance in Corsican blue tits (Parus caeruleus ogliastrae) as a model system. We found that blue tits breeding in rich broadleaved deciduous patches consistently laid eggs earlier in the season, and produced larger clutches and more fledglings of higher quality, than those breeding in poor evergreen patches. Also, parents, especially males, were in better physical condition in the broad-leaved deciduous than in the evergreen patches. Surprisingly, estimates of long-term effects of reproduction, such as recruitment rates of locally born offspring, did not differ between the two habitat types. Our results suggest that short-term breeding performance and phenotypic quality of both chicks and parents do not necessarily provide reliable information about contributions to following generations at a scale larger than that of the local study plot. Differences in reproductive performance between the two oak habitat types could not be attributed to densitydependent effects, differences in levels of nest predation, or differences in age structure of the birds. We suggest that habitats that are optimal for breeding are not necessarily optimal for survival after the breeding season.
The following values have no corresponding Zotero field: publisher: Springer-Verlag
Keywords: Habitat quality; Parus caeruleus; Predation; Quercus; reproduction

Habitat quality as a predictor of spatial variation in blue tit reproductive performance: a multi-plot analysis in a heterogeneous landscape - Lambrechts, MarcelM.; Caro, Samuel; Charmantier, Anne; Gross, Nicolas; Galan, Marie-Jo; Perret, Philippe; Cartan-Son, Mireille; Dias, PaulaC.; Blondel, Jacques; Thomas, DonaldW. (Oecologia, 2004)
Vertebrate studies have rarely investigated the influence of spatial variation in habitat richness on both short-term (breeding) and long-term (offspring recruitment) reproductive performance using simultaneously multi-patch, multi-habitat type and multi-year approaches at landscape level. Here we present results of such an approach using the influence of two oak tree (Quercus ilex, Q. humilis) species on reproductive performance in Corsican blue tits (Parus caeruleus ogliastrae) as a model system. We found that blue tits breeding in rich broadleaved deciduous patches consistently laid eggs earlier in the season, and produced larger clutches and more fledglings of higher quality, than those breeding in poor evergreen patches. Also, parents, especially males, were in better physical condition in the broad-leaved deciduous than in the evergreen patches. Surprisingly, estimates of long-term effects of reproduction, such as recruitment rates of locally born offspring, did not differ between the two habitat types. Our results suggest that short-term breeding performance and phenotypic quality of both chicks and parents do not necessarily provide reliable information about contributions to following generations at a scale larger than that of the local study plot. Differences in reproductive performance between the two oak habitat types could not be attributed to densitydependent effects, differences in levels of nest predation, or differences in age structure of the birds. We suggest that habitats that are optimal for breeding are not necessarily optimal for survival after the breeding season.
Keywords: Habitat quality; Parus caeruleus; Predation; Quercus; reproduction